Pengaruh Temperatur Pencampuran Terhadap Campuran Ac-Bc Yang Menggunakan Batu Gunung Kongkang Kesu’ - Iknasisus Saroan; Alpius; Eltrit Bima Fitrian (Program Studi Teknik Sipil UKI Paulus-Makassar, 2023)
In pavement layers, temperature is very important in affecting the strength of the asphalt mixture. Therefore, if the asphalt mixture is not at a certain temperature, the bond between aggregates will decrease and the mixture will become weak. The aim and purpose of this study was to test the mixing temperature of his AC-BC mixture using 5% asphalt. The methodology of this paper is AC-BC blend composition design and Marshall immersion testing to obtain residual Marshall stability values. It can be seen from the results of the tests carried out that values ​​for AC-BC mixtures were obtained for each variation at the mixture temperatures used, i.e. 120°C, 130°C, 140°C, 150°C and 160°. . C Stabilized value 1677.06 to 1940.40 kg, flow rate 3.87 to 2.92 mm, VIM 4.76% to 3.35%, VMA 16.41% to 15.17%%, VFB 70.01% to 77.92% Mixture temperature is Marshall parameter.